Spectrum of rare EGFR mutations in Indonesian lung adenocarcinoma: Findings from an 8-year analysis of 4,778 cases highlighting the need for advanced targeted therapies - Heriyanto, Didik S.; Trisnawati, Ika; Rachmadi, Lisnawati; Tenggara, Jeffry B.; Lau, Vincent; Gunawan, Andrew N.; Halim, Brigitta N.; Yuliani, Fara S.; Laiman, Vincent; Gondhowiardjo, Soehartati; Chuang, Hsiao-Chi (Narra J, 2025)
Lung cancer patients in Indonesia exhibit a high prevalence of epidermal growth factor receptor (EGFR) mutations, with a substantial proportion attributed to rare or uncommon variants. The clinical significance of rare EGFR mutations lies in their differential sensitivity to tyrosine kinase inhibitors (TKIs). While they are frequently resistant to first- and second- generation TKIs, they often respond to third-generation TKIs, necessitating tailored treatment options. The need for improving access to advanced targeted therapies in Indonesia also highlights the importance of conducting research on rare EGFR mutations. The aim of this study was to identify the spectrum and frequency of EGFR mutations in patients with lung adenocarcinoma in Indonesia. A cross-sectional observational study with total sampling was conducted from January 2016 to April 2024 to investigate EGFR mutation profiles in lung adenocarcinoma patients. Samples were acquired from patients with a confirmed anatomical pathology diagnosis from various healthcare centers across Indonesia. A total of 4,778 samples were analyzed using real-time quantitative polymerase chain reaction (RT-qPCR) on various specimen types to determine EGFR mutation prevalence and patterns. Associations between demographic data and EGFR mutation status were assessed. EGFR mutations were detected in 54.6% of samples, with common mutations (exon 19 deletions/insertions and point mutation L858R) comprising 76.2% of positive cases and rare mutations (exon 20 insertions, point mutation G719X, S768I, T790M, and L861Q) accounted for 20.3%. Significant associations were found between geographic origin, age, and sex with EGFR mutation status. This study confirms substantial genetic variability and geographical differences in EGFR mutations among Indonesian lung adenocarcinoma patients, emphasizing the urgent need for further research to prompt enhanced molecular diagnostics and targeted therapies in the region.